2013
DOI: 10.1111/anu.12043
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced lysine to arginine ratios reduced performance in juvenile cobia (Rachycentron canadum) fed high plant protein diets

Abstract: Cobia (8.4 ± 0.1 g body weight) were fed to satiation with three test diets of high plant protein‐based ingredients and different lysine to arginine ratios, and one commercial diet (currently used for cobia rearing in Vietnam as a control for growth) for 6 weeks. The test diets contained 206 g marine ingredients kg−1, including fishmeal, krill meal and fish protein concentrate (in order of high to low inclusion), while the rest of the dietary protein was a blend of soya and pea protein concentrate, wheat prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 89 publications
6
19
0
1
Order By: Relevance
“…(Olhão, Portugal). The experimental diets (Table ) were formulated based on previous results in cobia (Nguyen et al, ; Zhou et al, ). In the present study, crystalline DL‐methionine was added with different amount to make a diet deficient in methionine M9 (9.1 g/kg), a diet with sufficient methionine M12 (12.8 g/kg) and a diet with surplus methionine M16 (16.8 g/kg; Table ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Olhão, Portugal). The experimental diets (Table ) were formulated based on previous results in cobia (Nguyen et al, ; Zhou et al, ). In the present study, crystalline DL‐methionine was added with different amount to make a diet deficient in methionine M9 (9.1 g/kg), a diet with sufficient methionine M12 (12.8 g/kg) and a diet with surplus methionine M16 (16.8 g/kg; Table ).…”
Section: Methodsmentioning
confidence: 99%
“…The experimental tanks were fibreglass rectangular tanks (80 × 50 × 60 cm), with 200 L water filled, in two water recirculation subunits with continuous aeration (as described in Nguyen et al, ). Salinity was 29 ± 3.1 ppt, pH 7.8–8.3, oxygen 4.6 ± 0.5 mg/L and NH 3 < 0.03 mg/L.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it plays an important role in the synthesis of carnitine, which is important for the transport of long‐chain fatty acids into the mitochondrion for energy generation. In addition, dietary supplementation of lysine improves feed utilization (Li et al, ), nitrogen retention (Cao et al, ) and also reduce body lipid content of fish (Burtle & Liu, ; Nguyen, Rønnestad, Buttle, Lai, & Espe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lysine and methionine, which are used to synthesize nitrogen containing compounds, are the two most restrictive amino acids in the diets for finfish (Li et al., ) when fishmeal is replaced by high plant protein sources. Consequently, accurate assessment or knowing of these two amino acid requirements is needed to environmentally and cost‐effective of aquafeeds (Güroy et al., ; Mai, Zhang et al., ; van Nguyen, Rønnestad, Buttle, van Lai & Espe, ; NRC, ; Zhou et al., ). Recent research revealed that inclusion of lysine and methionine when high plant proteins containing and lowering protein level in diets could be enhanced the growth performance and digestive capacity of finfish (Davies & Morris, ; Gan et al., ; Gaylord & Barrows, ; Jiang et al., ; Kroeckel, Dietz, Schulz & Susenbeth, ; Rolland, Dalsgaard, Holm, Gómez‐Requeni & Skov, ).…”
Section: Introductionmentioning
confidence: 99%